Contribution of Basophils to Cutaneous Immune Reactions and Th2-Mediated Allergic Responses - Otsuka, Atsushi; Kabashima, Kenji (Frontiers in Immunology, 2015)
Basophils are potent effector cells of innate immunity and also play a role in T helper 2 (Th2)-mediated allergic responses. But, although their in vitro functions are well studied, their in vivo functions remain largely unknown. However, several mouse models of basophil depletion have recently been developed and used to investigate basophil functions. For example, in a croton oil-induced model of irritant contact dermatitis in conditionally basophil-depleted transgenic mice, we found that basophils rapidly infiltrate inflamed skin and subsequently induce infiltration of eosinophils. We also showed that basophils induce Th2 skewing upon epicutaneous sensitization with various haptens and peptide antigens. Intriguingly, basophils also promoted Th2 polarization upon protein antigen exposure in the presence of dendritic cells (DCs). The dermal DC subset associated with Th2 skewing was recently identified as CD301b+ DC. Such studies with basophil-deficient mouse models have significantly improved our understanding of the mechanisms involved in human immune-related diseases. In this review, we will focus on the relative contribution of basophils and DCs to Th2-mediated allergic responses.